Facial vein thrombophlebitis post facial skin infection: a case report and review of the literature - May Alshalawi; Amal Almoamary; Sulaiman Alrajhi; Raghad Alkanhal; Reema Alsogair; Danah Albarrak (SAGE Open Medical Case Reports, 2024)
This case report presents a rare instance of facial vein thrombophlebitis, a potentially serious complication, following a facial skin infection. A 33-year-old man known to have cerebral palsy, epilepsy on ventriculoparietal shunt, and kyphoscoliosis presented to the emergency department complaining of small facial wound and swelling for 1 week. The wound failed topical management and fever started to develop. His medications included quetiapine and levetiracetam. Investigations, including computed tomography, were carried out to rule out an extension to deep tissue. Management in the emergency department involved initial resuscitation with 500 mL of 0.9% normal saline and 1 L of lactated ringers, antibiotic coverage with piperacillin/tazobactam and vancomycin was given, and analgesia for pain control. This case highlights the potential for facial vein thrombophlebitis as a complication of facial skin infections. Early diagnosis and prompt initiation of appropriate management are crucial to prevent potentially fatal consequences.